Temperature Optimization and Addition of Aloe Vera Gel as Antibacteria In Coconut Oil-Based Liquid Soap - Rahman, Azizah; Paramita, Vita (Journal of Vocational Studies on Applied Research, 2021)
This study aims to determine the optimization of the ratio of coconut oil to KOH and temperature in the manufacture of liquid soap. In this study, the saponification reaction was used by reacting coconut oil with a strong base of KOH. The mole ratio between coconut oil and KOH used is 1:3, 1:4 and 1:5. The temperature used 3 points, there are 30oC, 40oC, and 50oC. Parameters observed were free fatty acid, pH, free alkali content, unsaponication fat content, density, and viscosity. The best results in the physiochemical test were running 4 (KOH ratio 5 and temperature 50oC) with pH 8, free alkali content of 0%, unsaponication fat content of 0.00175%, density 1.02 g/ml, viscosity 715.87 cP, and 1% free fatty acids. The critical value for the optimization of the liquid bath soap formula on the level of unsaponification fat based on RSM data is achieved at a KOH ratio of 4.28758 with a temperature of 62.40793oC.